Two-gap models: Post-keynesian death and neoclassical rebirth - Dieter Bender; Wilhelm Löwenstein (Ruhr-Universität Bochum, Institut für Entwicklungsforschung und Entwicklungspolitik (IEE), 2005)
In this paper we demonstrate that the Post-Keynesian Two-Gap Model merits its destiny as a ghost in economic discussions not only as a result of the well-known neoclassical criticism on its assumptions but also because of its general inconsistency. If adjusted for this inconsistency the Two-Gap Model, which stresses the limits to growth set by domestic savings (savings gap), and foreign currency reserves (foreign currency gap), turns into a Harrod-Domar-type One-Gap Model with domestic savings and capital inflows as sole determinants defining a country's limitations to grow economically. Therefore, the model can no longer be used, not even for analyzing the variation of a developing country's short term limits of growth brought about, e.g., by changes in the countries foreign trade strategies or in its obligations to pay interests on foreign debt. Such analysis is still common practice in the work of World Bank and the IMF. Instead we are proposing an extended structural closed economy one-sector neoclassical growth model which could be applied to a small open low income country (LIC) where the growth potential is highly restrained by too low domestic savings and by foreign exchange shortages. This model demonstrates that development strategies which rely on net borrowing abroad leads to a position of sustainable foreign indebtedness (provided that all capital imports are used for investment financing) but such strategy in general turn out to be immiserizing.
Keywords: 330; Postkeynesianische Wachstumstheorie; Entwicklungstheorie; Postkeynesianismus; Neoklassische Theorie; Theorie